Analysis of Suitability and Carrying Capacity for Ecotourism Purposes in the Sepanjang Beach Tourism Area - Clara Ammelia Sucahyo; Supriyadi; Rezky Lasekti Wicaksono; Galuh Masyithoh (International Journal of Marine Engineering Innovation and Research, 2025)
Sepanjang Beach offers a broad, long stretch of sand with a small quantity of coral and limestone hills that have turned into cliffs. Through its natural scenery, visitors become interested in visiting Sepanjang Beach. The purpose of the study was to analyze the level of suitability of tourism for sustainability. Meanwhile, research related to the area's carrying capacity was carried out to determine the ability of natural resources to maintain their function and quality to provide the recreational experience visitors want. For the sake of ecosystem availability, it is necessary to apply ecotourism principles to provide behavioral limits for humans as tourism actors to carry out recreational activities without reducing tourist satisfaction. The tourism suitability data collection technique uses 11 parameters: beach type; beach width; water depth; water bottom materials; beach slope; current speed; the brightness of the waters; closure of coastal land; dangerous biota; and availability of fresh water. While the carrying capacity of the area is calculated by calculating the economic level of the community around the tourist area, community contribution, visitor activities, the size of the area that visitors can use, length of visit, and the length of time the tourist area is open in one day. The results of the tourist suitability analysis at station 1 were 2.32, station 2 was 2.32, and station 3 was 2.2. The results show the area's carrying capacity is 240 people/day for fishing activities and 744 people/day for visitor recreation activities.